Microhabitat specialization of tropical rain-forest canopy trees in the Sovi Basin, Vitu Levu, Fiji Islands - Keppel, Gunnar; Tuiwawa, M .; Naikatini, A.; Rounds, I. (Cambridge University Press, 2011)
Island biotas often have lower species diversity and less intense competition has been hypothesized as a result. This should result in lower habitat specificity compared with mainland habitats due to larger realized niches. We investigate microhabitat associations of canopy trees with regard to differences in topography on an oceanic island (Viti Levu, Fiji) using twenty 10 × 60-m plots. We find high tree-species diversity (112 species with dbh > 10 cm in a total of 1.08 ha) and high endemism (c. 60%), compared with other islands in Western Polynesia. Our sample plots aggregate into three distinct groups that are mostly defined by micro-topography: (1) ridges and steep slopes (well-drained sites), (2) moderate slopes and ridge flats (moderate drainage), and (3) flats (poor drainage). Associations with microhabitat are found for more than 50% of the 41 most common species but only one species is apparently restricted to a single habitat. These findings are similar to other rain forests and demonstrate considerable niche differentiation among island rain-forest tree species.